Advanced financial accounting - Christensen, Theodore E.; Cottrell, David M.; Budd, Cassy (New York, NY : McGraw Hill Education, 2023)
"The Thirteenth Edition of Advanced Financial Accounting is an up-to-date, comprehensive, and highly illustrated presentation of the accounting and reporting principles and procedures used in a variety of business entities. Every day, the business press carries stories about merger and acquisition mania, the complexities of modern business entities, new organiza-tional structures for conducting business, accounting scandals related to complex business transactions, the foreign activities of multinational firms, the operations of governmental and not-for-profit entities, and bankruptcies of major firms. Accountants must understand and know how to deal with the accounting and reporting ramifications of these issues"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Accounting